Implementasi Teknologi Informasi Berbasis Web di Badan Amil Zakat Nasional (BAZNAS) - Nilda Susilawati; Andang Sunarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
National Amil Zakat Agency (BAZNAS) is a means of managing zakat in terms of collecting, distributing and using zakat. The existence of Baznas must continue to be improved through an institutional development strategy so that the management and utilization system can run efficiently, effectively and proportionally can have an impact on improving people's economic lives. One of the strategies used to improve the management of zakat institutions is to optimize the application of web-based information systems as a media to facilitate and improve the efficiency of zakat management in the collection, distribution and utilization of zakat. The results showed a new 34% BAZNAS in Indonesia that has used the SIMBA application As an application used to perform financial management reports, while for Public and Supporting only a few BAZNAS at the provincial level that has used this because of budget constraints and resources Human. Keywords: BAZNAS, Web-based Information System, Zakat